Forecast based pricing of weather derivatives - Wolfgang Karl Härdle; Brenda López-Cabrera; Matthias Ritter (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Forecasting based pricing of Weather Derivatives (WDs) is a new approach in valuation of contingent claims on nontradable underlyings. Standard techniques are based on historical weather data. Forward-looking information such as meteorological forecasts or the implied market price of risk (MPR) are often not incorporated. We adopt a risk neutral approach (for each location) that allows the incorporation of meteorological forecasts in the framework of WD pricing. We study weather Risk Premiums (RPs) implied from either the information MPR gain or the meteorological forecasts. The size of RPs is interesting for investors and issuers of weather contracts to take advantages of geographic diversification, hedging effects and price determinations. By conducting an empirical analysis to London and Rome WD data traded at the Chicago Mercantile Exchange (CME), we find out that either incorporating the MPR or the forecast outperforms the standard pricing techniques.
Keywords: G19; G29; G22; N23; N53; Q59; 330; weather derivatives; seasonal variation; temperature; risk premia; Wetter; Finanzderivat; Börsenkurs; Optionspreistheorie; Meteorologie; Prognoseverfahren; Theorie; Schätzung; USA